(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Adenomyosis is found during infertility work up in many women who delay pregnancy till their late thirties and in some women in their early age. Dysregulation of myometrial architecture and function and altered endometrial receptivity are among the possible mechanisms by which adenomyosis causes infertility. Adenomyosis and endometriosis may have similar pathogenesis as they have frequent association in women. Adenomyosis can be reliably diagnosed in symptomatic infertile women by non invasive means such as transvaginal ultrasound and magnetic resonance imaging as well as hysterosalpingography, hysteroscopy and laparoscopy. Early diagnosis by non-invasive means followed by surgical (adenomyomectomy) or non-surgical (MRgFUS) treatment of focal adenomyosis have promising effect on future pregnancy whereas diffuse severe adenomyosis have poor prognosis. Bangladesh J Obstet Gynaecol, 2015; Vol. 30(2) : 105-108